2019
DOI: 10.1007/s11357-019-00094-y
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory agent, OKN-007, reverses long-term neuroinflammatory responses in a rat encephalopathy model as assessed by multi-parametric MRI: implications for aging-associated neuroinflammation

Abstract: Lipopolysaccharide (LPS)-induced encephalopathy induces neuroinflammation. Long-term neuroinflammation is associated with aging and subsequent cognitive impairment (CI). We treated rats that had LPSinduced neuroinflammation with OKN-007, with an anti-inflammatory agent currently considered an anticancer investigational new drug in clinical trials for glioblastoma (GBM). Contrast-enhanced magnetic resonance imaging (MRI) (CE-MRI), perfusion MRI, and MR spectroscopy were used as methods to assess longterm (up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Additionally, genetic IGF-1 deficiency was shown to impair vascular function Csiszar et al, 2008;, including neurovascular coupling responses in rodent models . A recent (Towner et al, 2018) and (Towner et al, 2019). BOLD fMRI data are unpublished study suggested that systemic circulating IGF-1 protects against features of cognitive and sensorimotor decline with aging in male mice (Farias Quipildor et al, 2019).…”
Section: Age-related Igf-1 Deficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, genetic IGF-1 deficiency was shown to impair vascular function Csiszar et al, 2008;, including neurovascular coupling responses in rodent models . A recent (Towner et al, 2018) and (Towner et al, 2019). BOLD fMRI data are unpublished study suggested that systemic circulating IGF-1 protects against features of cognitive and sensorimotor decline with aging in male mice (Farias Quipildor et al, 2019).…”
Section: Age-related Igf-1 Deficiencymentioning
confidence: 99%
“…Long‐term neuroinflammation is associated with aging and subsequent cognitive impairment (CI). A recent study used parametric MRI approaches to assess cerebrovascular, blood–brain‐barrier (BBB), metabolic and free radical level changes associated with LPS‐augmented neuroinflammation, and found that LPS‐exposed rat brains had decreased relative cerebral blood flow (rCBF), increased BBB disruption, decreased N‐acetyl aspartate (NAA; a neuronal marker), and increased levels of free radicals detected in vivo, compared to saline‐treated controls (Figure 2) (Towner et al., 2018), (Towner et al., 2019). These findings imply that increased neuroinflammation results in cerebrovascular, neuronal metabolic and free radical changes, which are similar to the mechanistic alterations underlying age‐related BOLD fMRI change.…”
Section: Age‐related Impairment Of Neurovascular Coupling Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…OKN has been shown to be an anti‐inflammatory agent for age‐associated neuroinflammation in a lipopolysaccharide (LPS)‐induced encephalopathy rat model. 43 Currently, there is little data regarding the relationship between ELTD1 and inflammation, but future studies are needed to investigate this relationship. Further studies are being conducted to determine if Notch1 may be the master regulator of anti‐ELTD1 in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…to be an anti-inflammatory agent for age-associated neuroinflammation in a lipopolysaccharide (LPS)-induced encephalopathy rat model. 43 Currently, there is little data regarding the relationship be- be the master regulator of ELTD1. For instance, our data have demonstrated that key genes targeted by anti-ELTD1 antibody therapy, such as c-MET, Ki-67, BMP2 and VEGFR2 are all correlated with Notch1.…”
Section: Discussionmentioning
confidence: 99%